2014
DOI: 10.1002/hep.27382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic accuracy of aspartate aminotransferase to platelet ratio index and fibrosis‐4 index for detecting liver fibrosis in adult patients with chronic hepatitis B virus infection: A systemic review and meta‐analysis

Abstract: The aspartate aminotransferase-to-platelet ratio index (APRI) and fibrosis index based on the four factors (Fibrosis 4 index; FIB-4) are the two most widely studied noninvasive tools for assessing liver fibrosis. Our aims were to systematically review the performance of APRI and FIB-4 in hepatitis B virus (HBV) infection in adult patients and compare their advantages and disadvantages. We examined the diagnostic accuracy of APRI and FIB-4 for significant fibrosis, advanced fibrosis, and cirrhosis based on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
353
7
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(403 citation statements)
references
References 51 publications
23
353
7
4
Order By: Relevance
“…In addition, a recent metaanalysis regarding diagnostic accuracy of FIB-4 and APRI in patients with chronic hepatitis B infection showed that the mean AUROCs of FIB-4 and APRI for predicting cirrhosis were 0.78 and 0.72, while our data of FIB-4 and APRI were 0.771 and 0.761. Although the causes of liver diseases were different between their data and ours, our results were similar to their reports (29).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, a recent metaanalysis regarding diagnostic accuracy of FIB-4 and APRI in patients with chronic hepatitis B infection showed that the mean AUROCs of FIB-4 and APRI for predicting cirrhosis were 0.78 and 0.72, while our data of FIB-4 and APRI were 0.771 and 0.761. Although the causes of liver diseases were different between their data and ours, our results were similar to their reports (29).…”
Section: Discussionsupporting
confidence: 87%
“…The diagnostic accuracy of APRI and FIB-4 for significant fibrosis, advanced fibrosis, and cirrhosis was investigated in a systematic review [47]. They included 16 articles of APRI only, 21 articles of APRI and FIB-4 and two articles of FIB-4 for detecting different levels of liver fibrosis.…”
Section: Assessment Of Liver Fibrosismentioning
confidence: 99%
“…PLT is used in various predictive models of liver fibrosis and cirrhosis. In a meta-analysis, it has been shown that aspartate aminotransferase (AST)-PLT ratio index (APRI) and fibrosis-4 (FIB-4) index can identify liver fibrosis in CHB with a moderate sensitivity and accuracy (20). Chen et al (7) are the first investigators reporting an association between RDW and liver fibrosis and have reported that in the study, the most robust predictors in CHB patients namely RDW and PLT when used to get RPR have led to more accurate prediction of the risk of significant fibrosis (63.1%) and cirrhosis (73.7%) compared to AST-alanine aminotransferase (ALT) ratio (AAR), FIB-4 and APRI.…”
Section: Discussionmentioning
confidence: 99%